KUALITAS PERSAHABATAN DAN HARGA DIRI TERHADAP KEBAHAGIAAN PADA SISWA - Zahra, Lita; Ekasari, Agustina; Muslimah, Alfiana Indah (SOUL : Jurnal Pemikiran dan Penelitian Psikologi, 2025)
Happiness is one of the important factors in student success, both in academics, as well as in personal, social and career areas. Happiness has been shown to have a positive influence on a person's mental health and physical health. This study aims to determine the effect of friendship quality, and self esteem on happiness in students. The research respondents were 218 students using proportional random sampling technique. Data collection using psychological scales and interviews. Data analysis in this study used Spearman's Rho correlation technique and multiple linear regression test. Research shows there is a significant relationship between friendship quality and happiness with r = 0.256; p < 0.000. There is a relationship between self-esteem and happiness with r = 0.300; p < 0.000. The results of multiple regression tests show that there is an effect of friendship quality and self-esteem on happiness with a value of (F = 15.495. p <0.05).